Pedagogical Prudence as a Attitude of Teacher and Educator. the Reinterpretation of the Aristotelian-Thomist Concept of the Prudentiae Politicae in the Context of Pedagogical Practice - Machowski, Adam (21st century pedagogy, 2020)
In this article, I would like to attempt to reinterpret political prudence – a key skill for political action according to classical philosophy (Aristotle and Thomas Aquinas) – as a useful and even necessary skill for educators and teachers. This reinterpretation is made possible primarily by the fact that a significant part of the political works of classical authors is concerned with the upbringing and education of children and adolescents.